Evaluating Function-Based Social Stories™ With Children With Autism. (November 2015) - Pane, Heather M.; Sidener, Tina M.; Vladescu, Jason C.; Nirgudkar, Anjalee
Social Stories™ are often used with children with autism to provide information about appropriate behaviors in specific contexts. Although Social Stories™ often target reduction of problem behavior, there is limited research evaluating function-based Social Stories™ based on the results of experimental functional analyses. This study used a brief functional analysis to assist in developing a Social Story™ that matched the function of the target behavior for two boys with autism. The differential effects of a Social Story™ that matched the function of the behavior, a Social Story™ that did not match the function of the behavior, and a Social Story™ that described baseline were compared in an alternating treatments design. Results indicated that (a) the function-based Social Story™ plus functional communication training (FCT) was effective in decreasing target problem behavior and increasing target mands for both participants, (b) both participants selected the function-based Social Story™ during treatment preference evaluations, and (c) both participants maintained low levels of target problem behavior and maintained target mands when the Social Stories™ were removed.